2014
DOI: 10.1186/1471-2202-15-71
|View full text |Cite
|
Sign up to set email alerts
|

Changes in motor cortex excitability associated with temporal repetitive transcranial magnetic stimulation in tinnitus: hints for cross-modal plasticity?

Abstract: BackgroundMotor cortex excitability was found to be changed after repetitive transcranial magnetic stimulation (rTMS) of the temporal cortex highlighting the occurrence of cross-modal plasticity in non-invasive brain stimulation. Here, we investigated the effects of temporal low-frequency rTMS on motor cortex plasticity in a large sample of tinnitus patients. In 116 patients with chronic tinnitus different parameters of cortical excitability were assessed before and after ten rTMS treatment sessions. Patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, a clinical study with tinnitus patients correlated rTMS-induced (5 treatment days, 2000 pulses, 1 Hz stimulation frequency) increases in SICI with reduction in tinnitus questionnaire scores (Langguth et al, 2007 ). The same authors reported inverse effects in a later retrospective analysis of a larger sample, i.e., decrease in SICI in responding tinnitus patients over the course of the trial (Schecklmann et al, 2014 ). Three studies with major depressive patients and healthy controls report no effects of rTMS on SICI values (Eichhammer et al, 2007 ; Lee et al, 2013 ; Spampinato et al, 2013 ).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Furthermore, a clinical study with tinnitus patients correlated rTMS-induced (5 treatment days, 2000 pulses, 1 Hz stimulation frequency) increases in SICI with reduction in tinnitus questionnaire scores (Langguth et al, 2007 ). The same authors reported inverse effects in a later retrospective analysis of a larger sample, i.e., decrease in SICI in responding tinnitus patients over the course of the trial (Schecklmann et al, 2014 ). Three studies with major depressive patients and healthy controls report no effects of rTMS on SICI values (Eichhammer et al, 2007 ; Lee et al, 2013 ; Spampinato et al, 2013 ).…”
Section: Resultsmentioning
confidence: 94%
“…Also, although established, the parameters investigated here are not free from controversy: recently, a study systematically investigated the reliability of MEPs and found out that at least 30 repetitions are necessary for stable MEPs (Cuypers et al, 2014 ). This is in contrast with common practice, as can be seen in well referenced articles (Gerschlager et al, 2002 ; Schecklmann et al, 2014 ) and as suggested by textbooks (Siebner and Ziemann, 2007 ). In addition, further measurement methods (e.g., conditioning TMS pulse intensity and inter-stimulus intervals in the paired-pulse paradigms), for which we abstained from reporting them due to shortage of space, might also contribute to the high variability.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations